CARDI’s Experiences in addressing information needs for food and nutrition security in the Caribbean Agricultural and Rural Development Sector - Freitas, Claudette de (Technical Centre for Agricultural and Rural Cooperation, 2005)
Presentation on theme 2: Information Needs for Improved Decision Making about Food and Nutrition Security